The Impact of COVID-19 in Protected Areas Management: A Review of Emerging Challenges, Responses, and Future Research Lines in the Post-Pandemic Context - Medina-Chavarria, Maria E.; Saladié, Òscar; Gutiérrez, Aaron (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
The COVID-19 pandemic and the multiple associated changes in human activities and mobilities have implied the emergence of (new) challenges for the sustainable management of protected areas. With the objective of identifying and categorizing these emerging challenges, the responses implemented to address them, and their future implications, we developed a systematic literature review on the implications of COVID-19 crisis for protected areas management. Based on 56 articles published in 2020 and 2021, our findings offer (a) descriptions of the studies conducted, (b) multiscale effects of the pandemic on Protected Areas, (c) changes in the public use of Protected Areas during the pandemic, (d) managerial adaptation during the pandemic, (e) rethinking Protected Areas management both midand long-term, (f) and an emerging research agenda on Protected Areas. Overall, our results show broad agreement about the pandemic’s early cascading effects, both positive and negative, on the management of Protected Areas, and the behavioral and mobility patterns of their users. Three years have passed since the start of the pandemic, from which decision makers can leverage several lessons to be prepared for future crises; especially when it comes to achieving compatible levels of resilience and adaptability between the users of these areas and the institutions in charge of Protected Areas management.